Distributed IOS-SM transmission scheme with joint antenna and IOS unit selection for high-speed railway scenario - Qingfeng DING; Song WANG (Dianxin kexue)
A distributed intelligent omni-surface (IOS) -assisted spatial modulation (SM) transmission scheme was proposed to address the problem of transmission rate degradation caused by the high signal penetration loss in closed carriages in the high-speed railway scenarios.Firstly, SM technology was utilized to ensure that the indexed information section was not affected by penetration loss.Then, to reduce the high path loss and power loss of the long-range IOS windows, the distributed IOS was selected by traversal algorithm according to the principle of maximizing the received signal-to-noise ratio, and the best IOS window was activated to transmit the SM modulated information.Finally, to reduce the impact of the missing direct view path gain on the overall system performance, the antenna removal principle and the sequential selection method were used to dynamically and selectively activate the receiving antenna and IOS unit under the power consumption model.The simulation results show that the proposed scheme is more suitable for the high-speed railway wireless communication scenario than the conventional relay-forwarding and reconfigurable intelligence surface -SM (RIS-SM) schemes.And with the power loss model, the distributed IOS-SM scheme chosen by the combined antenna and IOS unit is still able to guarantee high performance transmission of the system.